Management and Point-of-Care for Tobacco Dependence (PROMPT): a feasibility mixed methods community-based participatory action research project in Ottawa, Canada - Pakhale, Smita; Kaur, Tina; Charron, Catherine; Florence, Kelly; Rose, Tiffany; Jama, Sadia; Boyd, Robert; Haddad, Joanne; Alvarez, Gonzalo; Tyndall, Mark (Université d'Ottawa | University of Ottawa, 2018)
To determine the feasibility of a Community-Based Participatory Tobacco Dependence Strategy (PROMPT) in the inner city population of Ottawa (Canada).
Keywords: epidemiology; health policy; public health; social medicine; Adolescent; Adult; Aged; Canada; Community-Based Participatory Research; Counseling; Feasibility Studies; Female; Harm Reduction; Humans; Male; Middle Aged; Peer Group; Poverty; Prospective Studies; Self Report; Smoking Cessation; Street Drugs; Tobacco Smoking; Tobacco Use Disorder; Young Adult; Point-of-Care Systems